Analisis Penyajian Laporan Keuangan Syariah Pada Baitul Mal Provinsi Aceh - Bustamam Bustamam; Ridwan Ibrahim; Dedy Saputra (Jurnal Dinamika Akuntansi dan Bisnis, 2015)
The objective of this research is to analyze the application Sharia financial statement at Baitul Mal Aceh. This research is qualitative research with descriptive analysis method that aims to provide an overview of research state of the object based on existing data and provide a comparative analysis between SFAS 109 is applied to the Baitul Mal Aceh. The result show that in general the Baitul Mal Aceh has adaopted SFAS 109. The financial statements at the Baitul Mal has adopted SFAS 109 which consists of the consolidated financial position, statement of activities, cash flow statement and notes to financial statements.